Implementation of Monetary Policy and the Central Bank's Balance Sheet - Schaechter, Andrea (Washington, D.C. : International Monetary Fund, 2001)
This paper discusses how the choice of central banks' operating targets influences the use of their monetary policy instruments and how the latter affect the central bank's balance sheet. This is of particular interest, since the monetary conditionality in IMF-supported programs has traditionally been linked to central bank balance sheet items. Quantity targeting tends to be practiced today mostly in countries in which money markets are not yet well-developed or a monetary aggregate is used as the intermediate target. Most other central banks prefer to target a short-term interest rate, which results in day-to-day changes in balance sheet items becoming endogenous.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet